All-ceramic restorations: A review of the literature - Abdulhadi Warreth; Yaser Elkareimi (Elsevier, 2020)
Objectives: Ceramics can simulate the visual character of the tooth substance successfully and are biocompatible materials. However, a wide range of ceramic materials and systems on the market are available for use in dentistry. Therefore, it is the aim of this article to provide an overview of dental ceramics, their classifications, methods of construction, and clinically relevant aspects that enable the reader to select the most appropriate ceramic for a particular clinical situation. Material and methods: The PubMed (MEDLINE) search engine was used to gather the most recent information on dental ceramics. The search was restricted to a ten-year period (January 1, 2010-December 31, 2019) and only English-language studies. A Boolean search of the PubMed data set was implemented to combine a range of keywords: (ceramics OR all-ceramics OR dental porcelain OR polycrystalline OR porcelain fused to metal OR ceramometal OR procera OR e max OR zirconia OR In-ceram OR Inlays OR Onlays OR Overlays OR Endocrown) AND (survival rate OR success rate OR clinical outcomes OR classification) AND (humans). Studies were also obtained by manual searches and from Google Scholar. Results: By using this process, 2173 articles and studies were obtained. More studies were also obtained by manual searches and from Google Scholar. The most relevant published studies were chosen and used in the current review. Conclusion: All-ceramic restoration use has increased in recent years. This increase has been attributed to patients' demand for good aesthetics and an improvement in the materials' mechanical and aesthetic properties as well as to required minimally invasive tooth preparation and the methods of fabrication. The success of ceramic restorations depends on several factors, such as selection of material, restoration design, occlusion, and cementation media.